PENERAPAN GAYA PENYUTRADARAAN MIKE LEIGH DALAM MEMBANTU PENGUATAN KARAKTER PENOKOHAN PADA FILM FIKSI “TROLL“ - Putra, Wayan Ari Pramana; Putra, Ida Bagus Hari Kayana; Prabhawita, Gede Basuyoga (CALACCITRA: JURNAL FILM DAN TELEVISI, 2025)
Film is a complex medium that combines visual, audio, and narrative elements to convey messages to the audience. In the world of filmmaking, the director plays a crucial role as the creative leader who translates the script into a visual work. This research aims to apply the directing style of Mike Leigh, known for his improvisational approach and deep character development, to enhance characterization in the short fiction film titled TROLL. The film addresses the social issue of toxic masculinity, which often has a negative impact on men’s mental health. The research methodology consists of three main stages: pre-production, production, and post-production. During the pre-production phase, extensive research, casting, and vision alignment among the production team are conducted. The production phase focuses on character exploration and realist cinematography techniques. The post-production phase involves visual and audio editing to ensure the final product aligns with the intended vision. The result is a 15-minute short film that successfully portrays the destructive effects of toxic masculinity through an emotional narrative and realistic characters. In conclusion, Mike Leigh’s approach proves effective in creating authentic characters and delivering a profound social message to the audience.